A practical and economical method for frontal sinus reconstruction after frontal craniotomy: A single-center experience with 140 patients - Guo, Youwei; Fu, Xianyong; Yin, Wen; Jiang, Zhipeng; Kuang, Yirui; Wu, Zhaoping; Cao, Yudong; Tan, Jun; Jiang, Xing-jun (Frontiers in Surgery, 2022)
Background: Frontal sinus exposure is a common consequence of frontal craniotomy. Cerebrospinal fluid leakage and infection are the major postoperative complications that may occur as a result of the open frontal sinus. The successful filling of open frontal sinus provides an approach to prevent significant complications caused by frontal sinus exposure. Objective: This article describes a new technique to reconstruct the exposed frontal sinus cavity with the combined application of gelfoam and vascularized pericranial flap. Methods: A total of 140 patients underwent frontal sinus reconstruction using gelfoam and vascularized pericranial flap between 2016 and 2021. Gelfoam was used to fill the frontal sinus, and vascularized pericranial flap was used to cover the frontal sinus when the bone flap is retracted. Results: Postoperative cerebrospinal fluid leakage and infection did not occur in any patient. Conclusion: Our results validated the effectiveness of our technique in the prevention of exposed frontal sinus-related postoperative complications.